Contextual functioning of phraseological units (a case of political speeches by Margaret Thatcher and John Major) - Trybukhanchyk, А. М.; Shkurat, Т. А. (My University, 2017)
Статтю присвячено аналізу особливостей функцюнування фра- зеологічних одиниць у політичних промовах британських прем'єр- міністрів Маргарет Тетчер і Джона Мейджора. На прикладах, запозичених з текстів промов, показано типи контекстів та особливості функцюнування в них фразеологічних одиниць.
The article analyzes the peculiaritbs of functbning of the phraseologbal units in political speeches by British Prime Ministers Margaret Thatcher and John Major. On the basis of examples which have been selected, it is shown the types of context where the idbms functbns are shown.
Keywords: політична промова; фразеологічна одиниця; politbal speech; phraseological unit; context; actualizer